2002
DOI: 10.1086/342329
|View full text |Cite
|
Sign up to set email alerts
|

Insights into SEN Virus Prevalence, Transmission, and Treatment in Community‐Based Persons and Patients with Liver Disease Referred to a Liver Disease Unit

Abstract: To document the prevalence and routes of transmission of SEN virus (SEN-V) in community-based individuals and patients referred to a liver disease unit, stored serum samples obtained from 160 Canadian Inuit and 140 patients with liver disease were tested for SEN-V DNA by polymerase chain reaction. In the community-based population, SEN-V was present in 57 (36%) of 160 persons. SEN-V-positive individuals tended to be younger and were more often male. Liver enzyme levels and serologic markers for hepatitis A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…Another report, Sugiura et al[ 18], in Japan reported that the two variants are not associated with acute or chronic hepatitis, although SENV-D might be a risk factor of fulminant hepatitis. Nevertheless, other studies have found only a weak association between SENV infection and liver disease [19,20,21]. In this study, no significant association was found between SENV infection and persistent elevated ALT value due to HBV/HCV infection or non-HBV/HCV origin, suggesting that the presence of SENV did not cause more severe liver damage in our patient group.…”
Section: Discussioncontrasting
confidence: 76%
“…Another report, Sugiura et al[ 18], in Japan reported that the two variants are not associated with acute or chronic hepatitis, although SENV-D might be a risk factor of fulminant hepatitis. Nevertheless, other studies have found only a weak association between SENV infection and liver disease [19,20,21]. In this study, no significant association was found between SENV infection and persistent elevated ALT value due to HBV/HCV infection or non-HBV/HCV origin, suggesting that the presence of SENV did not cause more severe liver damage in our patient group.…”
Section: Discussioncontrasting
confidence: 76%
“…The prevalence rates of SENV‐D and SENV‐H DNA in a HCV highly endemic area were similar to a contiguous area where HCV was not endemic 32 . In a community‐based population, SENV‐D and/or SENV‐H DNA positive rates were similar in subjects with or without HBV seropositivity (21.4% vs 36.6%; P > 0.5) 33 . Also, no significant difference in the prevalence rates of SENV in children with or without a history of blood transfusion was observed in Japan 23 .…”
Section: Discussionmentioning
confidence: 57%
“…It might be suggested that SENV‐H is preferentially a bloodborne infection while SENV‐D can be transmitted by other routes. Unfortunately, studies previously performed on a community‐based population did not analyse SENV genotype [3]. However, studies performed on IDU patients in the USA demonstrated a significantly higher frequency of SENV‐H when compared with SENV‐D [14].…”
Section: Discussionmentioning
confidence: 99%